DETERMINAN PERMINTAAN UANG DI INDONESIA - M Sabeth Abilawa; Rohman Siddiq (FEB Universitas Sultan Ageng Tirtayasa, 2016)
ABSTRACTMoney demand has an important role in monetary policy. Bank of Indonesia as a monetary authority has a task to keep the stability of the domestic value of money. The economic and monetary crisis cause the domestic value of money depreciate, in which it give an impact in the unstability of domestic money demand. The aim of this research is to investigate the influence of Gross Domestic Product (GDP),interest rate, exchange rate and the crisis dummy to money demand in Indonesia. This research uses secondary data from 1990 to 2011 and uses multiple linear regression with Ordinary Least Squares (OLS ) as research method. The results of the data analyzes show that Gross Domestic Product (GDP) and exchange rate have positive significant relationship with money demand in Indonesia, while interest rate shows has no significant relationship with money demand in Indonesia. Moreover, the crisis dummy variable has no significant relationship with money demand in Indonesia, with α =5 percent. Then, the value of coefficient determinant shows as many as 0.906591 or 90.6591 percent.Keywords: Money Demand, Gross Domestic Product, Interest Rate, Exchange Rate and The Crisis Dummy.ABSTRAKPermintaan uang mempunyai peranan penting di dalam kebijakan moneter. Bank Indonesia selaku otoritas moneter mempunyai tugas untuk menjaga nilai mata uang domestik. Krisis ekonomi dan moneter menyebabkan nilai mata uang domestic terdepresiasi, yang mana ini memberi dampak pada ketidakstabilan permintaan mata uang domestik. Tujuan dari penelitian ini adalah untuk melihat pengaruh dari Produk Domestik Bruto, suku bunga, kurs, dan dummy krisis terhadap permintaan uang di Indonesia. Penelitian ini menggunakan data sekunder dari tahun 1990 sampai 2011 dan menggunakan regresi berganda linier OLS sebagai metodologi penelitian. Hasil dari analisa data menunjukkan bahwa Produk Domestik Bruto dan kurs memiliki hubungan positif signifikan terhadap permintaan uang di Indonesia, sedangkan suku bunga menunjukkan tidak ada hubungan signifikan terhadap permintaan uang di Indonesia. Selanjutnya variabel dummy krisis tidak memiliki hubungan signifikan terhadap permintaan uang di Indonesia, dengan α =5 persen. Kemudian nilai koefisien determinasi sebesar 0.906591 atau 90.6591 persenKata Kunci: Permintaan Uang, Produk Domestik Bruto, Suku bunga, Kurs dan dummy krisis.